Contingency analysis of caregiver behavior: Implications for parent training and future directions. Issue 2 (27th April 2015) - Stocco, Corey S.; Thompson, Rachel H.
<x xml:space="preserve">Abstract</x> Parent training is often a required component of effective treatment for a variety of common childhood problems. Although behavior analysts have developed several effective parent‐training technologies, we know little about the contingencies that affect parent behavior. Child behavior is one source of control for parent behavior that likely contributes to the development of childhood problems and outcomes of parent training. We reviewed the evidence supporting child behavior as controlling antecedents and consequences for parent behavior. The implications for parent training are discussed, and recommendations for future research are suggested.